Synthesis and Characterization of ZSM-5 Catalyst for Catalytic Pyrolysis of Empty Fruit Bunches - Lutfia Rahmiyati; Susila Arita; Leily Nurul Komariah; Nazarudin Nazarudin; Oki Alfernando (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
ZSM-5 is known as a heterogeneous catalyst in the process of petroleum cracking. Zeolite has narrow pores so it needs synthesis to form mesopore so that reactant molecules can enter the active site in ZSM-5 mesopore. In this study, mesopore formation was carried out by adding Si/Al components with a ratio of 20 derived from tetraethyl orthosilicate, aluminum isopropoxide and TPAOH template with hydrothermal process. The resulting ZSM-5 was characterized using x-ray diffraction, scanning and electron microscopy (SEM). The XRD characterization results showed that the ZSM-5 synthesized to form mesopore was seen from a fairly high peak intensity in the range at 2-theta were 8.11, 9.01°; 23.27°; 23.49°; and 24.13°. The results of this study already have the same structure as the commercial ZSM-5. Characterization of SEM-EDS showed that Si-Al and Na elements in ZSM-5 were 96.43%, 3.56% and 0% wt, respectively. With a magnification of 20000x, this cluster is quite homogeneous even though the crystallization formed is not well aggregated. This ZSM-5 catalyst will be applied to the process of biomass into bio-oil.